Energy transfer processes in organic and inorganic materials for photovoltaic devices - Menelaou, C (2015)
This thesis is concerned with energy transport processes in a series of low-bandgap copolymers, solution processable hybrid organic-inorganic perovskite materials, and donor-acceptor triad dyes which are used in photovoltaic cells and solar concentrator devices. These processes are investigated using time-resolved photoluminescence (PL) spectroscopy techniques which allow the investigation of transport processes with sub-ps time resolution. Two donor-acceptor-donor triad dyes composed of perylene bisimide units are compared, and rapid energy transfer (< 2 ps) from the donor to a central bay-substituted PBI unit is observed in both molecules. For the linear molecule, in which the transition dipole moments corresponding to the lowest singly excited state are all aligned along the molecule long-axis, such rapid energy transfer is shown to be consistent with predictions of a modified Förster model which takes into account both the delocalisation of the excitation and the short donor-acceptor separation. When the dipole moments of the donor units are perpendicular to that of the central acceptor however, this model is found to strongly underestimate the energy transfer. The energy transfer is found to arise due to a combination of both through-space (Förster type) and through-bond energy transfer, the latter of which is mediated by molecular torsions which break orthogonality and enable conjugation between the two units. This rapid energy transfer also coincides with either retention or rotation of polarisation between absorption and emission. These dyes are therefore shown to be promising candidates for use in luminescent solar concentrators (LSC), as rapid intramolecular energy transfer and control of the emission polarisation are two features which can help to reduce self-absorption and escape losses in LSC devices. The effect of chemical structure on the morphology, energy transport properties and overall photovoltaic device efficiency is determined for a series of low-bandgap polymers comprising benzodithiophene donor and benzothiadiazole acceptor units. Photovoltaic devices incorporating polymer:fullerene blends are found to yield devices with power conversion efficiencies of up to 6%, with the highest PCE observed in devices which form films exhibiting a very low degree of crystallinity in X-ray diffaction patterns and a corresponding low surface roughness in thin films. The influence of crystallite formation on energy transport is probed by time resolved PL quenching of polymer films on a TiO2 quenching layer. Exciton diffusion lengths in these films are standard for low-bandgap polymers, ranging from 4 to 7.5 nm. The diffusion length is found to be higher in films with a higher degree of crystallinity, however direct PL quenching measurements on polymer:PCBM films show however that the vast majority of generated excitons are found to reach an interface and dissociate within 1 ps, showing that exciton diffusion does not present a bottle-neck for device efficiencies. From these observations it is concluded that the boundaries between crystalline and amorphous domains may impede charge extraction at the charge densities found during photovoltaic operation. Finally, the distance over which electron-hole pairs can diffuse before decay or trapping is investigated in two organic-inorganic hybrid perovskite structures (CH3NH3PbI3-xClx) by monitoring the rate and degree of PL quenching in the presence of either an electron or hole acceptor material. The diffusion lengths observed in these materials are on the order of 100 nm for the triiodide perovskite (x = 0), and over 1 μm in the mixed halide material (x > 0). These diffusion lengths are extremely long compared with those observed in other solution processable materials and explain the very high power conversion efficiencies that have been reported in photovoltaic cells containing these and similar perovskite materials. The longer diffusion lengths in particular correlate with good power conversion efficiency when a planar device geometry is used. Similar cells using the triiodide material however show poor efficiencies, attributed to the smaller diffusion length in this material. Application of the PL quenching technique to determine diffusion lengths is therefore shown to be a useful and simple method by which the suitability of a given perovskite material for use in a planar PV cell can be determined.